Governing the climate-energy nexus institutional complexity and its challenges to effectiveness and legitimacy - Bäckstrand, Karin; Nasiritousi, Naghmeh; Skovgaard, Jakob 1977-; Widerberg, Oscar; Zelli, Fariborz (Cambridge University Press, 2020)
Combating climate change and transitioning to fossil-free energy are two central and interdependent challenges facing humanity today. Governing the nexus of these challenges is complex, and includes multiple intergovernmental and transnational institutions. This book analyses the governance interactions between such institutions, and explores their consequences for legitimacy and effectiveness. Using a novel analytical framework, the contributors examine three policy fields: renewable energy, fossil fuel subsidy reform, and carbon pricing. These fields are compared in terms of their institutional memberships, governance functions and overarching norms. Bringing together prominent researchers from political science and international relations, the book offers an essential resource for future research and provides policy recommendations for effective and legitimate governance of the climate-energy nexus. Rooted in the most recent research, it is an invaluable reference for researchers, policymakers and other stakeholders in climate change and energy politics.